2011
DOI: 10.3109/00365513.2011.580858
|View full text |Cite
|
Sign up to set email alerts
|

Serum testosterone levels during early pregnancy in patients developing preeclampsia

Abstract: The concentrations of serum T, SHBG and the T/SHBG-ratio in early pregnancy do not predict the development of preeclampsia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…This aligns with an older study which showed the free testosterone level in maternal serum remained within range of non-pregnant women until 28 weeks gestation (Bammann, Coulam, & Jiang, 1980). Maternal salivary testosterone levels at each gestational period did not differ by fetal sex, consistent with reports based on maternal serum testosterone in pregnancy (Carlsen et al, 2006;Tuutti et al, 2011;van de Beek et al, 2004). There was also no difference in postpartum maternal salivary testosterone for women who gave birth to boys versus girls.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This aligns with an older study which showed the free testosterone level in maternal serum remained within range of non-pregnant women until 28 weeks gestation (Bammann, Coulam, & Jiang, 1980). Maternal salivary testosterone levels at each gestational period did not differ by fetal sex, consistent with reports based on maternal serum testosterone in pregnancy (Carlsen et al, 2006;Tuutti et al, 2011;van de Beek et al, 2004). There was also no difference in postpartum maternal salivary testosterone for women who gave birth to boys versus girls.…”
Section: Discussionsupporting
confidence: 89%
“…Maternal salivary testosterone levels at each gestational period did not differ by fetal sex, consistent with reports based on maternal serum testosterone in pregnancy (Carlsen et al, ; Tuutti et al, ; van de Beek et al, ). There was also no difference in postpartum maternal salivary testosterone for women who gave birth to boys versus girls.…”
Section: Discussionsupporting
confidence: 87%
“…Circulating androgens concentrations increase during normal gestation in women (Berger, Repke, & Woodruff, ; McClamrock & Adashi, ; Mizuno, Lobotsky, Lloyd, Kobayashi, & Murasawa, ; Rivarola, Forest, & Migeon, ) and both, the fetus and the placenta, produce androgens that enter the maternal circulation (Makieva, Saunders, & Norman, ). In pregnant women, circulating maternal serum T is low during the first trimester and increases during gestation (Kerlan, Nahoul, Le Martelot, & Bercovici, ; Makieva et al, ) independent of offspring sex (Troisi et al, ; Tuutti et al, ; van de Beek, van Goozen, Buitelaar, & Cohen‐Kettenis, ).…”
Section: Androgens In Women and Female Cattlementioning
confidence: 99%
“…In pregnant women, circulating maternal serum T is low during the first trimester and increases during gestation (Kerlan, Nahoul, Le Martelot, & Bercovici, 1994;Makieva et al, 2014) independent of offspring sex (Troisi et al, 2003;Tuutti et al, 2011;van de Beek, van Goozen, Buitelaar, & Cohen-Kettenis, 2009).…”
Section: Androgens In Women and Female Cattlementioning
confidence: 99%
“…Male spontaneously hypertensive rats (SHR), which exhibit some signs of a programming model such as smaller size at birth when compared to Wistar-Kyoto control rats, exhibit androgendependent increases in blood pressure and albuminuria that are independent of renal cortical angiotensin II levels and oxidative stress (Sullivan et al, 2007). In contrast, a female specific form of hypertension during pregnancy, preeclampsia, is reportedly not to be influenced by the levels of circulating testosterone levels during pregnancy (Tuutti et al, 2011). Interestingly, the cardio-renal protective effects of estrogens has not been a universal finding (Salazar et al, 2008).…”
Section: Sex Steroidsmentioning
confidence: 99%